P141 CORRELATION BETWEEN TAKO–TSUBO SYNDROME AND OCCULT CANCER. (18th May 2022) - Isola, U; Pittau, R; Marchetti, M; Boscarelli, D; Tuveri, M; Caggiari, L; Maiani, S; Contini, F; Montisci, R
Abstract: Introduction: Tako–Tsubo Syndrome ("TTS") is a cardiomyopathy characterized by an acute reversible left ventricular dysfunction, mainly triggered by emotional or physical stress. Several variants have been reported, including reverse TTS, characterized by hypokinesia of basal segments and hyperkinesis of the apical ones. TTS has a clinical presentation similar to acute coronary syndrome but without evidence of obstructive coronary artery disease. A surprising association between TTS and cancer arose out of recent studies. Case Presentation: 74–year–old patient got to the emergency room of our hospital for the appearance, apparently in the health, in the absence of physical or emotional stress of oppressive chest pain. On the ECG, there was evidence of ST–segment elevation in inferior leads, for which urgent coronary angiography was performed. It did not show significant stenotic lesions nor evidence of elevated troponin values. The Echocardiogram showed hypokinesia of the basal segments and hyperkinesis of the mid–apical ones, with EF 40%. In the following days, the patient performed MRI–heart with detection of LGE of the intramyocardial type (non–ischemic pattern) in correspondence with the inferior wall in the medioventricular area. During hospitalization on routine chest x–ray, hypodiaphanous image was found in the left apex for which an HR CT scan of the chest was performed which a lesion in the left apical lung area with spiculated margins of a heteroplastic nature, associated with multiple bilateral lesions suggestive of secondaryism. Therefore, the patient was taken over by the Oncology service. Conclusions: Such case confirms the association between TTS and occult cancer. In the absence of obvious physical or emotional stress that may explain the onset of TTS, it is important to research for any silent neoplastic pathology. The literature shows that the prevalence of malignant diseases is high in patients with TTS. Recent studies have pinpointed the activation of the sympathetic nervous system promotes cardiac inflammation by upregulating ICAM–1 and the expression of p53. Furthermore, inflammation can lead to the activation of p38 MAP Kinase, thus contributing to myocardial stunning. The specific role of inflammation as a cofactor of adrenaline–induced stunning deserves further investigation in the specific context of malignant tumors, which are frequently associated with an enhanced inflammatory state.